Pengaruh Modal Manusia dan Pengembangannya terhadap Kinerja Auditor Kementerian Kelautan dan Perikanan - Septina Suyanti, Dungdung; Muljono, Pudji; Vitayala S.Hubeis, Aida (Jurnal Manajemen dan Organisasi, 2023)
Auditors are internal supervisors whose role is to provide assurance and consultation so that the Ministry of Marine Affairs and Fisheries' programs, activities and budgets are carried out transparently and accountable. Good auditor performance can improve organizational performance and encourage the implementation of good governance. This study aims to analyze the characteristics of human capital and human capital development that affect the performance of auditors of the Ministry of Marine Affairs and Fisheries. The sampling technique uses non probability sampling. The type of non probability sampling used in this study is saturated sampling where all respondents are used as examples. The data were analyzed with descriptive statistics and Structural Equation Modeling Partial Least Square (SEM-PLS) analysis by first testing the questionnaire through validity and reliability tests. The results showed that auditor performance is not influenced by human capital development but has a significant important role for human capital. Human capital development indicators that are best reflected in a row are on-the-job training, career support and off-the-job training. Good human capital plays an important role for auditors in meeting work quantity, time and quality targets. This study also found that human capital can mediate the effect of human capital development on auditor performance. Knowledge, experience, professional proficiency and personality traits are important human capital indicators in this study.